The Impact of Mobile Information Communication and Technology (ICT) in Ubiquitous Health Sciences Libraries. Issue 3 (2nd July 2016) - Taylor, Deborah M.
ABSTRACT: Health sciences libraries (HSLs) are predisposed to systemic changes that result from the increased use of mobile information communication and technology (ICT). The impact of mobile ICTs requires libraries, especially health sciences libraries (HSLs), to remain viable by adapting to the modifications needed to support the information behaviors of their clients. The use of mobile ICTs is instrumental in how library client's access digital information. Many HSLs have yet to consistently define their purpose and mission in midst of changing library information ecology. Additionally, "library as place" requires HSLs to redefine the purpose of physical space in order to align with the information needs of their clients. Literature revealed a need for HSLs to provide ongoing professional development, which includes basic technology proficiencies as a way to effectively connect and interact with the growing number of digitally born clients. A review of selected literature was examined to gain clarity on the impact of mobile ICTs in health sciences libraries. This article will discuss the influence of mobile ICTs and its implication for future practice in health sciences libraries. Two additional areas impacted by mobile ICTs, "library as place" and the library's changing information ecology, were explored. The primary research question that guided this review was, How has mobile ICTs impacted health science libraries? The intent of this question was to study key factors found in the literature, which impacted health sciences libraries as a result of mobile ICTs use.